INSECURITY IN THE SOUTHEASTERN STATES OF NIGERIA AND MULTI-PURPOSE COOPERATIVE SOCIETIES BUSINESS PERFORMANCE (Journal of the Management Sciences, 2024)
This study was carried out to evaluate the Effect of Insecurity on the Performance of MultiPurpose Cooperative Businesses in Southeast, Nigeria. The study encompasses Monday's sit-at-home, Kidnapping and Ritual killing and Herders/farmers clash to reduce multipurpose business performance in the Southeast. Simple Percentage Method and Tables; Research Questions were analyzed using the Correlation method and Multiple Regression for hypothesis testing. Taro Yamane formula was used to determine the Sample Size 365. The findings show that Monday's sit-at-home, Kidnapping and Ritual killing, Banditry and Herders/farmers clash have significantly influenced southeast cooperative business performance activities. In line with the findings, Insecurity like, agitators' Monday-sit-athome order, kidnapping for ransom & ritual killing, banditry menace, and herders and farmers clashes affect the performance of cooperative business. The correlation result indicated that Monday-sit-at-home affected the business activities of cooperative societies. The Pearson r statistic showed a value of -.605** (p=.000). The p-value of .000 is less than .05 and thus concludes that the relationship is significant. Therefore, question two shows that the agitators' Monday-sit-at-home order influences the business activities of cooperative societies in Southeast Nigeria. As such, this study recommends that Cooperatives should work with local law enforcement and security agencies to implement security measures that can protect cooperative members from potential threats.
Keywords: Insecurity; Southeast of Nigeria; Multi-Purpose Cooperative Societies; Business Performance.